Factors Related to the Diagnosis of Tuberculosis Meningitis in Children at the National Children's Hospital from 2019 to 2024 - Thi Van Anh, Tran; Viet Hai, Phan; Thien Hai, Do; Cuong Loi, Trinh; Trung Kien, Pham; Viet Hung, Dau; Van Dem, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 2, 2025)
Objective: Some factors related to the diagnosis of tuberculous meningitis at the National Children's Hospital (2019 - 2024). Subjects and methods: Cross-sectional descriptive study of 50 children from 1 month to 15 years old diagnosed and treated for tuberculous meningitis at the Center for Tropical Diseases, National Children's Hospital. Results: There were 50 patients with tuberculosis meningitis in nearly 6 years from January 2019 to October 2024. The average time of diagnosis from the onset of symptoms was 19 days. The earliest was 4 days, and the latest was 56 days. The median treatment time at a medical facility was 8 days. The majority (68% of patients) were diagnosed with central nervous system infections, with nearly 70% choosing third-generation cephalosporin antibiotics alone or in combination with aminoglycosides or vancomycin. Patients diagnosed at stages II and III accounted for 82%. Some factors, including age, altered consciousness, signs of increased meningeal enhancement and ventricular dilation on MRI/CT, and cellular components in cerebrospinal fluid, especially the number of lymphocytes > 50%, were related to the time of diagnosis of tuberculous meningitis. Conclusion: Tuberculous meningitis in children at the National Children's Hospital is often diagnosed late with clinical stages II and III according to the British Medical Research Council. Age, altered consciousness, signs of increased meningeal enhancement and ventricular dilation on MRI/CT, and cellular components in cerebrospinal fluid are factors related to the diagnosis of tuberculous meningitis.